Flexible porous graphene film and preparation method thereof
By mixing the graphene oxide dispersion with the salt solution, drying the mold method and reducing the hydroiodic acid, the existing graphene film preparation methods and insufficient conductivity were solved, and a porous graphene film with excellent flexibility and mechanical strength was successfully prepared.
Patent Information
- Application Number
- CN202211481869.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-24
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2042-11-24
AI Technical Summary
The existing graphene film preparation methods are cumbersome and have low preparation efficiency. The prepared graphene film has low porosity and electrical conductivity that cannot be further improved, which limits its application range.
By mixing the graphene oxide dispersion with the salt solution, a mixed solution of salt-containing graphene oxide is formed, and a salt-containing particle graphene oxide film is dried in the mold. Then, chemical reduction is performed using hydroiodic acid to remove oxygen-containing functional groups in the salt-containing particles and graphene oxide structure to form a porous graphene film.
The preparation of macroscopic continuous, flexible porous graphene films is realized, with excellent flexibility and high mechanical strength, and is suitable for large-scale promotion and use.
Smart Images

Figure CN115893383B_ABST
Abstract
Description
[Technical field]
[0001] The invention relates to the technical field of graphene films, in particular to the technical field of flexible porous graphene films and preparation methods thereof. [Background technology]
[0002] Graphene is a new type of carbon material with a hexagonal honeycomb two-dimensional grid structure composed of carbon atoms through sp2 hybridization. The layered stacking of nano-scale graphene sheets is easy to form a two-dimensional membrane structure, which has high electron mobility and tensile fracture strength, and can be used as a raw material for supercapacitors, energy storage and sensors.
[0003] The existing chemical methods for preparing graphene films mainly include vacuum filtration, liquid phase electrophoretic deposition and gas-liquid surface self-assembly. Specifically, He et al. (He G, Chen H, Zhu J, et al. Synthesis and characterization of graphene paper with controllable properties via chemical reduction [J]. Journal of Materials Chemistry, 2011, 21 (38): 14631-14638.) used hydrazine hydrate solution as a reducing agent, and obtained graphene dispersions with different reduction degrees by a chemical conversion method of liquid phase reduction of graphene oxide dispersions, and then used vacuum filtration to prepare graphene film electrode materials with different conductivity; Niu et al. (Niu Z, Chen J, Hng HH, et al. A Leavening Strategy to Prepare Reduced Graphene Oxide Foams [J]. Advanced Materials, 2012, 24(30): 4144-4150.) The graphene oxide dispersion treated with ultrasound is vacuum filtered to obtain a graphene oxide film, and then reduced with hydrazine hydrate vapor to prepare a graphene film; Yang Quanhong disclosed a conductive graphene film and a self-assembly preparation method thereof in the invention patent with announcement number CN101559944B, which can obtain a large-area graphene oxide film by self-assembly of the graphene oxide dispersion at the gas-liquid interface.
[0004] However, the above-mentioned graphene film preparation methods basically have the defects of being relatively cumbersome, too low preparation efficiency and poor electrochemical performance of the prepared graphene film. Constructing a porous structure can effectively improve the conductivity of graphene-based two-dimensional materials, thereby expanding the application range of graphene-based two-dimensional materials. However, due to its special conjugated electronic structure, graphene materials have extremely strong van der Waals forces, are prone to agglomeration and stacking, and ultimately greatly limit the preparation method of flexible porous graphene films. Therefore, how to improve the low porosity and electrical conductivity of traditional graphene films in a simple and easy way, in order to explore and develop graphene films with good comprehensive performance is a problem to be solved urgently. [Summary of the invention]
[0005] The purpose of the present invention is to solve the problems in the prior art and to propose a flexible porous graphene film and a preparation method thereof, which can prepare a macroscopically continuous, flexible and porous graphene film with excellent flexibility and high mechanical strength. The entire production process is simple and easy to control, the process flow is short, the production efficiency is high, and the reproducibility is strong. The size of the prepared film is stable and easy to cut, and it is very suitable for large-scale promotion and use.
[0006] To achieve the above object, the present invention is implemented through the following technical solutions:
[0007] A method for preparing a flexible porous graphene film comprises the following steps:
[0008] a) mixing the graphene oxide dispersion with a salt solution to obtain a salt-containing graphene oxide mixed solution;
[0009] b) pouring the salt-containing graphene oxide mixed solution prepared in step a) into a mold and drying it to obtain a salt-containing particle graphene oxide film;
[0010] c) chemically reducing the salt-containing granular graphene oxide film prepared in step b) with a reducing agent, and then washing and drying the film to obtain a finished product.
[0011] Preferably, in step a), the mass blending ratio of graphene oxide to salt in the salt-containing graphene oxide mixed solution is 1:1 to 1.5.
[0012] Preferably, the concentration of the graphene oxide dispersion is 5 to 10 mg / mL, and the concentration of the salt solution is 0.1 to 1 mol / L.
[0013] Furthermore, the concentration of the graphene oxide dispersion is 7-10 mg / mL, and the concentration of the salt solution is 0.4-0.6 mol / L.
[0014] Preferably, in the step a), the mixing temperature is 10-60°C.
[0015] Preferably, in step a), the salt is one or more of sodium carbonate, sodium bicarbonate, calcium carbonate, calcium bicarbonate, potassium carbonate, potassium bicarbonate, zinc carbonate and magnesium carbonate.
[0016] Preferably, in step b), drying is performed under vacuum conditions at a drying temperature of 30 to 200° C. and a drying time of 4 to 24 hours.
[0017] Preferably, in the step c), the reducing agent is hydroiodic acid.
[0018] Preferably, in step c), the reduction temperature is 80-300° C. and the reduction time is 6-36 hours.
[0019] Furthermore, in the step c), the reduction temperature is 190-210° C. and the reduction time is 6-8 hours.
[0020] Preferably, in step c), anhydrous ethanol and deionized water are used as detergents for washing in sequence, the drying temperature is 30 to 200° C., and the drying time is 4 to 24 hours.
[0021] The flexible porous graphene film is prepared by the above preparation method.
[0022] Beneficial effects of the present invention:
[0023] The present invention mixes a graphene oxide dispersion with a salt solution and adopts a mold method to dry to obtain a graphene oxide film containing salt particles. The salt particles can be blended in the graphene oxide to form an intercalation structure, and then hydroiodic acid is used as a reducing agent to remove the salt particles and the oxygen-containing functional groups in the graphene oxide structure in one step. At the same time, under the action of the gas generated by the reduction reaction, the graphene sheet layer is further intercalated. Finally, after sufficient washing and drying, a macroscopically continuous, flexible and porous graphene film with excellent flexibility and high mechanical strength is obtained. The graphene film can be applied to many fields such as superconductivity, energy storage and photoelectric conversion. The raw materials are all abundant in source, low in price and green and environmentally friendly. The entire production step is simple and easy to control, the process flow is short, the production efficiency is high, the reproducibility is strong, the size of the prepared film is stable and easy to cut, and it is very suitable for large-scale promotion and use.
[0024] The features and advantages of the present invention will be described in detail through embodiments in conjunction with the accompanying drawings.
Brief Description of the Drawings
[0025] Figure 1 is a scanning electron microscope image of the flexible porous graphene film prepared in Example 2;
[0026] Figure 2is a physical picture of the flexible porous graphene film prepared in Example 2 when being bent;
[0027] Figure 3 This is a scanning electron microscope image of the pure graphene film prepared in Example 7. [Specific implementation method]
[0028] Embodiment 1:
[0029] First, 9 mL of 7 mg / ml graphene oxide aqueous dispersion and 1 mL of 0.1 mol / L Na2CO3 solution were stirred at 30°C to obtain a salt-containing graphene oxide mixed solution. Subsequently, 9 mL of the prepared salt-containing graphene oxide mixed solution was transferred into a 3×10 cm tetrafluoroethylene mold using a pipette. After the salt-containing graphene oxide mixed solution was evenly spread, the mold was placed in a 60°C vacuum oven for 12 hours to obtain a salt-containing (Na2CO3) granular graphene oxide film. Next, hydroiodic acid and the prepared salt-containing (Na2CO3) granular graphene oxide film were placed in a high-temperature reactor and reduced at 200°C for 8 hours. After the chemical reduction was completed, the reduced film was placed in anhydrous ethanol for ultrasonication for 10 to 20 minutes. After the ultrasonic solution had no color change, the pre-washed film was washed with deionized water, and then the film that had been washed twice was dried at 80°C for 4 hours to obtain a finished product.
[0030] Embodiment 2:
[0031] First, 9 mL of 7 mg / ml graphene oxide aqueous dispersion and 1 mL of 0.5 mol / L Na2CO3 solution were stirred at 40°C to obtain a salt-containing graphene oxide mixed solution. Subsequently, 9 mL of the prepared salt-containing graphene oxide mixed solution was transferred into a 3×10 cm tetrafluoroethylene mold using a pipette. After the salt-containing graphene oxide mixed solution was evenly spread, the mold was placed in a vacuum oven at 80°C and dried for 12 hours to obtain a salt-containing (Na2CO3) granular graphene oxide film. Next, hydroiodic acid and the prepared salt-containing (Na2CO3) granular graphene oxide film were placed in a high-temperature reactor and reduced at 200°C for 10 hours. After the chemical reduction was completed, the reduced film was placed in anhydrous ethanol for ultrasonication for 10 to 20 minutes. After the ultrasonic liquid solution had no color change, the pre-washed film was washed with deionized water, and then the film that had been washed twice was dried at 60°C for 6 hours to obtain a finished product.
[0032] Embodiment three:
[0033] First, 9 mL of 6 mg / ml graphene oxide aqueous dispersion and 1 mL of 0.5 mol / L Na2CO3 solution were stirred at 30°C to obtain a salt-containing graphene oxide mixed solution. Subsequently, 6 mL of the prepared salt-containing graphene oxide mixed solution was transferred into a 3×10 cm tetrafluoroethylene mold using a pipette. After the salt-containing graphene oxide mixed solution was evenly spread, the mold was placed in a 60°C vacuum oven for 12 hours to obtain a salt-containing (Na2CO3) granular graphene oxide film. Next, hydroiodic acid and the prepared salt-containing (Na2CO3) granular graphene oxide film were placed in a high-temperature reactor and reduced at 200°C for 8 hours. After the chemical reduction was completed, the reduced film was placed in anhydrous ethanol for ultrasonication for 10 to 20 minutes. After the ultrasonic liquid solution had no color change, the pre-washed film was washed with deionized water, and then the film that had been washed twice was dried at 80°C for 4 hours to obtain a finished product.
[0034] Embodiment 4:
[0035] First, 9 mL of 6 mg / ml graphene oxide aqueous dispersion and 1 mL of 1 mol / L Ca2CO3 solution were stirred at 50°C to obtain a salt-containing graphene oxide mixed solution. Subsequently, 9 mL of the prepared salt-containing graphene oxide mixed solution was transferred into a 3×10 cm tetrafluoroethylene mold using a pipette. After the salt-containing graphene oxide mixed solution was evenly spread, the mold was placed in a vacuum oven at 100°C for 6 hours to obtain a salt-containing (Ca2CO3) granular graphene oxide film. Next, hydroiodic acid and the prepared salt-containing (Ca2CO3) granular graphene oxide film were placed in a high-temperature reactor and reduced at 150°C for 12 hours. After the chemical reduction was completed, the reduced film was placed in anhydrous ethanol for ultrasonic treatment for 10 to 20 minutes. After the ultrasonic solution had no color change, the pre-washed film was washed with deionized water, and then the film that had been washed twice was dried at 100°C for 4 hours to obtain a finished product.
[0036] Embodiment five:
[0037] First, 9 mL of 6 mg / ml graphene oxide aqueous dispersion and 1 mL of 0.5 mol / L mixed solution of Na2CO3 and Ca2CO3 (the mass ratio of Na2CO3 and Ca2CO3 is 1:1) are stirred at 30°C to obtain a salt-containing graphene oxide mixed solution. Subsequently, 3 mL of the prepared salt-containing graphene oxide mixed solution is transferred into a 3×10 cm tetrafluoroethylene mold using a pipette. After the salt-containing graphene oxide mixed solution is evenly spread, the mold is placed in a vacuum oven at 60°C and baked for 12 hours to obtain a salt-containing (Na2CO3 and Ca2CO3) granular graphene oxide film. Next, hydroiodic acid and the prepared salt-containing (Na2CO3 and Ca2CO3) granular graphene oxide film were placed in a high-temperature reactor respectively and reduced at 200°C for 8 hours. After the chemical reduction was completed, the reduced film was placed in anhydrous ethanol and ultrasonicated for 10 to 20 minutes. After the ultrasonic solution had no color change, the pre-washed film was washed with deionized water, and then the film that had been washed twice was dried at 80°C for 4 hours to obtain the finished product.
[0038] Embodiment six:
[0039] The flexible porous graphene film prepared in Example 2 was photographed by a field thermal emission scanning electron microscope. Figure 1 , it can be seen that the salt particles of Na2CO3 have been fully removed, and the membrane has a significant porous structure. Specifically, during the chemical reduction, the salt particles will undergo double decomposition under the action of hydroiodic acid and produce carbon dioxide, water and salt ions. Among them, CO2 will exert a certain force on the membrane when it overflows, making the membrane have a significant porous structure, while the salt ions can be removed in the subsequent washing and drying process. In addition, see Figure 2 , it can be seen that the flexible porous graphene film can easily achieve 180° bending, thus proving its super flexibility.
[0040] Embodiment seven:
[0041] Taking Example 2 as an example to prepare a comparative material, the specific operation process is as follows:
[0042] First, 9 mL of 7 mg / ml graphene oxide aqueous dispersion was fully stirred at 40 ° C, and then all of it was transferred into a 3×10 cm tetrafluoroethylene mold using a pipette. After the graphene oxide aqueous dispersion was evenly spread, the mold was placed in a vacuum oven at 80 ° C for 12 hours to obtain a graphene oxide film. Next, hydroiodic acid and the prepared graphene oxide film were placed in a high-temperature reactor and reduced at 200 ° C for 10 hours. After the chemical reduction was completed, the reduced film was placed in anhydrous ethanol and ultrasonicated for 10 to 20 minutes. After the ultrasonic solution had no color change, the pre-washed film was washed with deionized water, and then the film that had been washed twice was dried at 60 ° C for 6 hours to obtain a pure graphene film.
[0043] Performance test: The pure graphene film was photographed by a field thermal emission scanning electron microscope, and the resistance data of the pure graphene film and the flexible porous graphene film prepared in Example 2 were measured by Keithley Ke2400s.
[0044] See also Figure 3 , it is observed and analyzed that the internal structure of the pure graphene film is stacked layer by layer to form a regular and dense internal structure, and no pores appear. In contrast, a porous structure appears inside the porous flexible graphene film prepared in Example 2. This proves that the addition of carbonates or bicarbonates is the key to forming a porous flexible graphene film. In addition, the porous graphene film has obvious pores, and its porosity is about 50%. Dependent on this porous structure, the apparent thickness of the porous graphene film is also greater than the thickness of the pure graphene film.
[0045] In addition, under the same preparation conditions, the volume resistivity of the pure graphene film is 0.42Ω·cm, while the volume resistivity of the porous flexible graphene film prepared in Example 2 is 0.6Ω·cm, which is comparable to the volume resistivity of the pure graphene film, proving that the flexible porous graphene film has excellent flexibility.
[0046] The above embodiments are intended to illustrate the present invention, not to limit the present invention. Any solution that is a simple transformation of the present invention belongs to the protection scope of the present invention.
Claims
1. A method for preparing a flexible porous graphene film, characterized in that: The steps include: a) mixing a graphene oxide dispersion with a salt solution to obtain a salt-containing graphene oxide mixed solution; the salt is one or more of sodium carbonate, sodium bicarbonate, calcium carbonate, calcium bicarbonate, potassium carbonate, potassium bicarbonate, zinc carbonate and magnesium carbonate; the mass blending ratio of graphene oxide to salt in the salt-containing graphene oxide mixed solution is 1:1 to 1.5; b) pouring the salt-containing graphene oxide mixed solution prepared in step a) into a mold and drying it to obtain a salt-containing particle graphene oxide film; drying is performed under vacuum conditions at a drying temperature of 30 to 200° C. and a drying time of 4 to 24 hours; c) chemically reducing the salt-containing granular graphene oxide film prepared in step b) with a reducing agent, and then washing and drying in sequence to obtain a finished product; washing is carried out in sequence with anhydrous ethanol and deionized water as detergents, the drying temperature is 30 to 200° C. and the drying time is 4 to 24 hours; the reducing agent is hydroiodic acid.
2. The method for preparing a flexible porous graphene film according to claim 1, characterized in that: In the step a), the mixing temperature is 10-60°C.
3. The method for preparing a flexible porous graphene film according to claim 1, characterized in that: In the step c), the reduction temperature is 80-300° C. and the reduction time is 6-36 hours.
4. The method for preparing a flexible porous graphene film according to claim 3, characterized in that: In the step c), the reduction temperature is 190-210° C. and the reduction time is 6-8 hours.
5. A flexible porous graphene film prepared by the preparation method according to any one of claims 1 to 4.
Citation Information
Patent Citations
Conductive graphene film and self-assembly preparation method thereof
CN101559944B
Graphene elastic thin film and preparation method thereof
CN106185906A
Super-flexible high thermal conductive grapheme film and preparation method thereof
US20190023575A1